2019
DOI: 10.25226/bboc.v139i4.2019.a7
|View full text |Cite
|
Sign up to set email alerts
|

Notes on bird breeding activity in a lowland forest in south-west Brazilian Amazonia

Abstract: BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 10 publications
1
9
0
1
Order By: Relevance
“…Despite Leptotila rufaxilla to be commonly found within the forest (Ingels 1982, Schulenberg et al 2010, in ZP this species appears to nest in open areas with cultivated plants or in forest edge. Overall, the characteristics of the breeding were similar to those recorded for many Neotropical Doves (Skutch 1949, Snow & Snow 1964, Marini et al 2010, Lima et al 2019. The shape and dimensions nest of L. r. reichenbachii in Argentina (Bodrati & Salvador 2013) and L. r. rufaxilla in north Brazil (Oniki & Willis 1983) were similar to those found in this work, like "shallow platforms".…”
Section: Discussionsupporting
confidence: 87%
“…Despite Leptotila rufaxilla to be commonly found within the forest (Ingels 1982, Schulenberg et al 2010, in ZP this species appears to nest in open areas with cultivated plants or in forest edge. Overall, the characteristics of the breeding were similar to those recorded for many Neotropical Doves (Skutch 1949, Snow & Snow 1964, Marini et al 2010, Lima et al 2019. The shape and dimensions nest of L. r. reichenbachii in Argentina (Bodrati & Salvador 2013) and L. r. rufaxilla in north Brazil (Oniki & Willis 1983) were similar to those found in this work, like "shallow platforms".…”
Section: Discussionsupporting
confidence: 87%
“…Some of the areas chosen for nesting by the species are subject to intense anthropic activity, indicating an adaptability to these areas (Ingels et al 1999). A recent study found that the species also breeds in another forest fragment 30 km from Rio Branco (Lima et al 2019), indicating reasonable adaptation to the fragmented landscape of eastern Acre. The shape and colour of the eggs were compatible with previous descriptions from various regions (Ihering 1900, Hellebrekers 1942, Thurber 2003, Vasconcelos et al 2003.…”
Section: Discussionmentioning
confidence: 98%
“…Some of the areas chosen for nesting by the species are subject to intense anthropic activity, indicating an adaptability to these areas (Ingels et al 1999). A recent study found that the species also breeds in another forest fragment 30 km from Rio Branco (Lima et al 2019), indicating reasonable adaptation to the fragmented landscape of eastern Acre.…”
Section: Discussionmentioning
confidence: 98%
“…Their nests are often discovered when the adult is flushed by an approaching observer, thereby revealing the eggs. Despite being common and widespread, there are relatively few detailed studies of the species' breeding biology, especially in Amazonia (Snethlage 1935, Oniki & Willis 1982, Lima et al 2019. We report nesting data for Common Pauraque from an urban forest fragment in south-west Amazonian Brazil and provide new information on its breeding season in Brazil based on citizen science data.…”
Section: Appendixmentioning
confidence: 97%